HYDROPHILIC MODIFICATION ON THE SURFACE OF POLYPROPYLENE BASED ULTRAFILTRATION MEMBRANE - Kusuma Wardani, Anita
Polypropylene (PP) based ultrafiltration membrane is one of the promising membranes to be developed in Indonesia due to its high chemical and mechanical stability, lower price, and readily available. PP membranes have been widely applied for gas separation and oil filtration, while the application of PP membrane for drinking water treatment is still limited due to its hydrophobic nature. The hydrophobic nature of PP membrane leads to low water flux and high fouling tendency. To solve this issue, hydrophilic modification on PP membrane is required. Polydopamine coating is a simple method that can be applied to improve the hydrophilicity of PP membrane surface, thus increase the water flux as well as prevent fouling formation. In this study, hydrophilic modification on PP hollow fiber ultrafiltration membrane was conducted by polydopamine coating with variation of dopamine concentration, coating time, and air permeation during coating process. The results showed that coating by 3 g/L of dopamine for 3 hours with the addition of air permeation through membrane lumen with flow rate of 5 L/min was able to decrease the water contact angle from 110±2.2° to 66.5±3.2°. Meanwhile, the pure water flux of PP membrane at 2 bar increased from 186.3±13.7 L/(m2.h) to 511.2±23.2 L/(m2.h). In this study, polyethylene glycol (PEG) and/or polyvinylpyrrolidone (PVP) were also added into the coating solution to obtain PP membrane with higher hydrophilicity. The addition of PVP with concentration of 2 g/L has been proven to be able to decrease the water contact angle of PP membrane up to 45.2±2.8°, while the water contact angle only decreased to 54.0±3.4° and 55.4±3.5° by addition of PEG1000 dan PEG6000 with concentration of 2 g/L, resepctively. The addition of PEG played important role on increasing porosity on polydopamine layer thus led to the increase of pure water flux to 530-542 L/(m2.h), while the pure water flux for PVP addition was only 501.3±29.2 L/(m2.h) at 2 bar. Furthermore, the addition of both additives with PEG/PVP ratio at 1:2 was able to obtain water contact angle of 45.2±1.9º and pure water flux of 511.3±18.6 L/(m2.h) at 2 bar, 3 times higher than pure water flux of the unmodified PP membrane. The improved hydrophilicity of PP membrane was also indicated by the increase of surface free energy of PP membrane up to 50% after modified by polydopamine coating with addition of PEG and PVP. In this study, the effect of hydrophilic modification on separation performance and organic fouling tendency of the modified PP membranes was also evaluated through humic acid filtration. The results showed that polydopamine coating was able to improve permeate flux up to 1.18 times higher than the unmodified PP membrane, while the rejection of humic acid increased from 63% to 69%. Hydrophilic modification by polydopamine coating could also reduce irreversible fouling tendency on PP membrane, that is indicated by the increase of flux recovery ratio (FRR) from 68.59% to 86.14-87.71% after modification. The hydrophilic modification was also able to decrease both intrinsic and fouling resistances of PP membrane. Evaluation on stability of polydopamine layer also showed good results, that indicated by only 1-5% change of pure water flux and water contact angle after 30 days of storage in demineralized water and isopropyl alcohol (IPA) solution as well as after backflushed at 5 bar for 15 minutes. The hydrophilicity of polydopamine layer on PP membrane was also unchanged after the modified PP membranes were immersed in alcohol, strong acid, and weak alkali solutions for 8 hours. The results of thermogravimetric analysis (TGA) also indicated that polydopamine layer could protect the PP membrane from heating gas thus the mass loss of the modified PP membrane was only 8% after heated up to 450°.